Alternância no uso dos modos indicativo e subjuntivo em orações subordinadas substantivas: uma comparação entre o português do Brasil e o francês do Canadá - Vieira, Marta Mara Munguba (2007)
The purpose of this work is to analyze the use of the indicative mood, instead of the subjunctive prescribed by the normative grammar, in complement clauses introduced by the conjunction que in Brazilian Portuguese. Contexts of use of the subjunctive according to grammatical prescription, and contexts of fluctuation on the use of that verbal mood were analyzed, in an attempt to investigate what interferes on the choice of the mood by the user of the language. This study is based on North-American Functional Linguistics theoretical perspective, oriented to analyzing language in use, in the light of the principles of grammaticalization and markedness. The results obtained support that the contexts that favor the indicative over the subjunctive are those composed by a complement clause functioning as a direct object the unmarked clause of all complement clauses and by a verb on the main sentence that belongs to the semantic field of low certainty, corresponding to the epistemic sub-mode the unmarked category of the deontic sub-mode. The results indicate that pragmatics and semantics factors influence the language user on the choice of the verbal mood. This research also presents comparative data on the use of the indicative mood in place of the subjunctive in Brazilian Portuguese and Canadian French, aiming to providing suggestions on language teaching